Translation Analysis Of Adverb In The Fault In Our Stars Translated By Inggrid Dwijani Nimpoemo - Kurniawati, Yullinda, Dr. Dwi Haryanti, M.Hum (2016)
The purposes of this research are to describe the translation of adverb in the novel The Fault in our Stars and to describe the translation quality of the novel The Fault in Our Stars.The type of this research is descriptive qualitative. The data of this research are the adverbs found in The Fault in our Stars novel. The researcher uses documentation to collect the data. The researcher also uses comparative method to analyze the data of the research. From 3585 data found by researcher there are 212 translation shift. First, the data of translation shifts belong to category shifts, there are 101 data or 47.2%; 62 data or 29.2% adverb is translated into adjective; 18 data or 8.5% adverb is translated into verb; 20 data or 9.4% adverb is translated into noun; 1 data or 0.5% adverb is translated into preposition. Second, the data of translation shift belong to level shifts, there are 111 or 53.8%; 27 data or 12.7% adverb is translated into adverb phrase; 50 data or 23.6% adverb translated into adjective phrase; 18 data or 8.5% adverb is translated into verb phrase; 16 data or 7.6% adverb translated into noun phrase. So, adverb is translated into adjective is more dominate than the other. From 3585 total counts of the data there are 3476 data or 97% belongs to accurate, 83 data or 2.3% belongs to less accurate, and 26 data 0.7% belongs to inaccurate. From 3585 total counts of the data there are 2484 data or 97.2% belongs to acceptable, 75 data or 2.1% belongs to less acceptable, and 26 data or 0.7% belongs to unacceptable. From 3585 total counts of the data there are 3552 data or 99.1% belongs to highly readable, 5 data or 0.1% belongs to quite readable, and 28 data or 0.8% belongs to hardly readable.